Knowledge of the Peruvian population about the actions that make up the preventive triad of rabies transmitted by bite of domestic dogs - León, Daphne (2022)
The aim of this study was to determine the knowledge of the Peruvian population about the actions that make up the preventive triad of rabies that were reported in the National Survey of Budgetary Programs 2020. The independent variables were the departments of the country (includes Callao), area (urban and rural), geographic region (coast, highlands and jungle) and urban sociodemographic strata (A, B, C, D and E). The study retrieved information from 52 791 surveys, finding that the most frequently recognized component of the preventive triad was going to the health facility (85.4%), followed by washing the wound with plenty of soap and water (43.1%) and, by last, identify the aggressor animal (15.5%). These components were recognized more frequently in urban areas and on the coast of the country. A positive and direct correlation was found between knowledge of the components of the preventive triad and socioeconomic level. Among endemic departments to rabies, Arequipa presented a better proportion of favourable responses compared to Puno. It is concluded that it is necessary to disseminate knowledge of the components of the preventive triad, especially in areas endemic to canine rabies to increase attitudes and practices that impact on the reduction of the risk of virus transmission and the development of the disease in humans.